New landscapes of conflict: land-use competition at the urban–rural fringe. (19th May 2019) - Jensen, David; Baird, Timothy; Blank, Gary
Abstract: Land-use conflict research generally focuses on conflicts where pre-existing opponents respond to the introduction of a new unwanted land-use. We select a 2008 land-use conflict to explore an understudied scenario: urban–rural fringe (URF) expansion can introduce new opposing stakeholders into areas with pre-existing unwanted land-uses. We use spatial analysis methods to measure the rate and direction of URF expansion in relation to a vacated cement facility that had been approved for revitalisation in 2008, motivating a land-use conflict between competing stakeholders. Findings indicate that the cement facility and surrounding land-uses had been continuously used for similar noxious activities since 1964, but URF expansion changed the area's surrounding landscape from rural-majority to urban-majority prior to the 2008 land-use conflict. The association between URF expansion and space-related drivers of land-use conflict is a necessary consideration when studying increasingly urbanised landscapes.